EFFECTIVENESS OF VISCERAL MANUAL THERAPY IN THE TREATMENT OF INFANT COLIC: PILOT STUDY - García-Marqués , S; Chillón-Martínez , R; González-Zapata , S; Rebollo-Salas , M; Jiménez-Rejano , J J (Cuestiones de Fisioterapia, 2017)
Introduction: infant colic is one of the most frequent consultations in primary care in children. But few health stra-tegies can address this problem with scientific certainty. Objective is to verify the effectiveness of visceral manual therapy in the treatment of infantile colic. Material and method: a pilot study with 30 children with infant colic to verify the effectiveness of the physical therapy through manual therapy (visceral manual therapy and massage) in the treatment of infant colic. The severity of colic as well as the improvement of colic was determined using «In-fant Colic Severity Questionnaire». Results: it was verified that there were no differences between the groups at the beginning of the study. It was observed that in both groups there was a statistically significant difference in the severity of infant colic between pre-intervention and post-intervention values. In addition, the improvement achieved by the infants in the experimental group (mean = 4.28 SD = 2.19) was significantly higher [difference in means = 2.20 CI (0.6; 3.79)] than in the control group (mean = 2.07 SD = 2.09) and an effect size (Cohen d = 1) very large.Conclusions: visceral manual therapy could be effective in the treatment of infant colic